Health care seeking behaviour and expenditure pattern among Scrub Typhus patients attending a tertiary care hospital in Mysore city - Jayanandan, Rajesh; Manjunath, Renuka; Kulkarni, Praveen (International Journal of Research in Medical Sciences, 2017)
Background: Scrub typhus is one among the re-emerging infectious diseases throughout the world. Various studies conducted across India reveals that its public health importance is increasing. This study was conducted 1) To describe the socio-demographic and epidemiological profile of patients admitted with scrub typhus. 2) To assess the health care seeking behaviour of these patients. 3) To estimate the cost factors incurred in the current episode of illness. Methods: This prospective study was conducted from January to December 2013 among all lab confirmed cases of scrub typhus admitted to department of medicine and pediatrics of JSS Hospital, Mysore. The study subjects were interviewed with a pre-tested and structured questionnaire. Data regarding socio-demographic profile, epidemiological profile, disease outcome, health care seeking behaviour and cost factors incurred with current episode of illness were collected. Data entry and analysis were done with SPSS.v.22.0 using descriptive statistics like mean, standard deviations and inferential statistics like chi-square test. Results: Among 192 patients tested positive by Weil-Felix test and/or Immuno-Chromatographic Test (ICT) for scrub typhus majority 105 (54.7%) were males and were predominantly 135 (70.3 %) from rural areas. Mostly 172(89.6%) were unaware of any mite bite in the past. Majority 167 (87.0%) of them had visited atleast three Health Care Facilities (HCF) for treatment. The mean ± SD total duration of illness was 15.6 ± 4.1 days. Most 104 (54.2 %) of them had suffered from illness for 11-15 days. Majority 175 (91.1%) of them had recovered while 3 (1.6%) of them had succumbed to the condition. The median Total direct cost, total indirect cost and overall total cost were Rs. 7500 (7000-9500), Rs. 3000 (2500-3500) and Rs. 10500 (10000-13000) respectively. Most 104 (54.2%) of them spent from money borrowed from others, followed by 78 (40.6%) spent Out Of Pocket (OOP). Conclusion: People from rural areas, unskilled workers and children were affected predominantly. With timely diagnosis and appropriate treatment, significant morbidity and mortality could be prevented. Promotion of various public and private health insurance schemes among public would minimise the OOP expenditure and prevents debts.